2018
DOI: 10.1111/liv.13862
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent impact of proton pump inhibitors on the clinical course of spontaneous bacterial peritonitis

Abstract: High dosages of proton pump inhibitors are associated with an adverse outcome in patients with spontaneous bacterial peritonitis. Thus, indication for high-dosage proton pump inhibitors therapy should be evaluated carefully in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 30 publications
2
36
0
2
Order By: Relevance
“…Patients were recruited from the Hannover ascites cohort (HAC) . The in‐ and exclusion criteria have been described previously . Briefly, all 1011 consecutive, hospitalised patients that underwent paracentesis at the Hannover Medical School between January 2012 and June 2016 were considered.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were recruited from the Hannover ascites cohort (HAC) . The in‐ and exclusion criteria have been described previously . Briefly, all 1011 consecutive, hospitalised patients that underwent paracentesis at the Hannover Medical School between January 2012 and June 2016 were considered.…”
Section: Methodsmentioning
confidence: 99%
“…But evidence has revealed that PPIs influence the gut microbiota and potentially increase the risk for enteric infections, notably by increasing the risk for Clostridium difficile infection, which could lead to bacterial translocation . Use of PPIs predisposes to the development of complications associated with decompensated cirrhosis . However, little is known about the impact of PPIs on intestinal permeability in patients with cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Proper attention has not been paid to the prevention and treatment of cirrhotic patients with peptic ulcer in current practice. One reason was that the application of proton pump inhibitors (PPI) in liver cirrhosis was still on doubt [23][24][25][26], and the other reason was that the antibiotics for eradicating H. pylori may aggravate liver injury, especially for decompensated liver cirrhosis patients. Some studies proved that PPI did not increase the incidence of SBP [27], while other studies verified that PPI can induce SBP [28].…”
Section: Discussionmentioning
confidence: 99%